A first insight into the genomic background of Ilex pubescens (Aquifoliaceae) by flow cytometry and genome survey sequencing - Peng Zhou; Qiang Zhang; Jiao Li; Fei Li; Jing Huang; Min Zhang (BMC Genomics, 2023)
Abstract Background Ilex pubescens is an important traditional Chinese medicinal plant with many naturally occurring compounds and multiple pharmacological effects. However, the lack of reference genomic information has led to tardiness in molecular biology research and breeding programs of this plant. Results To obtain knowledge on the genomic information of I. pubescens, a genome survey was performed for the first time by next generation sequencing (NGS) together with genome size estimation using flow cytometry. The whole genome survey of I. pubescens generated 46.472 Gb of sequence data with approximately 82.2 × coverage. K-mer analysis indicated that I. pubescens has a small genome of approximately 553 Mb with 1.93% heterozygosity rate and 39.1% repeat rate. Meanwhile, the genome size was estimated to be 722 Mb using flow cytometry, which was possibly more precise for assessment of genome size than k-mer analysis. A total of 45.842 Gb clean reads were assembled into 808,938 scaffolds with a relatively short N50 of 760 bp. The average guanine and cytosine (GC) content was 37.52%. In total, 197,429 microsatellite motifs were detected with a frequency of 2.8 kb, among which mononucleotide motifs were the most abundant (up to 62.47% of the total microsatellite motifs), followed by dinucleotide and trinucleotide motifs. Conclusion In summary, the genome of I. pubescens is small but complex with a high level of heterozygosity. Even though not successfully applied for estimation of genome size due to its complex genome, the survey sequences will help to design whole genome sequencing strategies and provide genetic information support for resource protection, genetic diversity analysis, genetic improvement and artificial breeding of I. pubescens.